Three new species of Gymnopus and Mycena (Agaricales, Basidiomycota) from Northwestern China - Fan, LongFei; Wang, BiYue; Ma, TianFu; Li, Bin; Ma, JianWei; Lei, XuTao; Bao, NingHui (Frontiers in Microbiology, 2024)
Members of the genera Gymnopus and Mycena are vital for litter decomposition in tropical and humid temperate forests. In this study, the difference in morphological features among Gymnopus gansuensis, Gymnopus subsepiiconicus, and Mycena glabera was confirmed by DNA data. Gymnopus gansuensis and Gymnopus subsepiiconicus showed separate relationships with other species in the ITS and nLSU combined dataset utilized for the phylogeny of Gymnopus sect. Impudicae. In addition, Gymnopus gansuensis is characterized by pileus honey yellow at the center, margin pinkish buff to buff, stipe pinkish buff to fuscous, and basidiospores elliptic to briolette. Gymnopus subsepiiconicus is characterized by pileus clay buff to grayish brown at the center, margin pinkish buff to fawn, stipe dark brown to fuscous, and basidiospores elliptic. Based on the combined dataset of the ITS and TEF-1α, Mycena glabera has been detected as a separate lineage in the phylogenetic studies of Mycena sect. Calodontes. The ecological behaviors of the new species are described with illustrations.